BENTUK DAN FUNGSI DEIKSIS TEMPORAL DALAM BAHASA JERMAN DAN BAHASA INDONESIA - Yunanfathur Rahman (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2017)
This article describes the problem of temporal deixis in German and Indonesian. German as flexion-language has differences to Indonesian as inflexion-language. Researcher tried to explain about the form and function of deictic and non-deictic lexemes time in German and Indonesian. The analysis based on the standardized language in written data.The results showed some conclusions about the form and function of the time lexeme which are deictic and non-deictic in German and Indonesian. Lexemes can refer to the time before the moment of utterance, at a time of utterance, and the time after the utterance. Time lexemes also appear through tenses. German has three tenses, namely past tense, present tense and future tense. Time lexemes based on the rotation of the earth, such as the alternation of day into night is actually not deictic. But these lexeme can be deictic if joining the demonstrative pronouns, past markers, future marker, or symmetrical time lexeme.